Dba-free palladium intermediates of the Heck-Matsuda reaction - MacHado, Angelo H. L.; Milagre, Humberto M. S. [UNESP]; Eberlin, Livia S.; Sabino, Adão A.; Correia, Carlos Roque D.; Eberlin, Marcos N. (Royal Society of Chemistry (RSC), 2013)
The dba-free Heck-Matsuda reaction was investigated via direct ESI-MS(/MS) monitoring. Palladium species involved in the reduction of Pd(ii) during a Wacker type reaction and several dba-free arylpalladium transient complexes were detected and characterized. Based on these findings, a more comprehensible catalytic cycle for this pivotal reaction is suggested. © 2013 The Royal Society of Chemistry.
Keywords: Catalytic cycles; Heck-matsuda reactions; Palladium intermediates; Palladium species; Transient complexes; Wacker-type reactions; Chemistry; Positive ions; Reaction intermediates